Spatial, Functional, and Constructive Analysis of the Water Resource at the Archaeological Center of Tipon, Cusco, Peru, 2023 - Doris Esenarro; Jorge Lescano; Brenda Chalco; Nicole Tapia; Jesica Vilchez Cairo; Carlos Vargas Beltran; Cecilia Arriola; Rosa Ruiz Reyes (Heritage)
The objective of this research is to analyze the spatial, functional, and constructive aspects of the water resource at the Archaeological Center of Tipon, given the lack of awareness towards the timely preservation of archaeological heritage, the deterioration of the terraces, and the contamination of the rivers adjacent to the archaeological site due to the discharge of waste into the water bodies. The methodology employed consists of a site study analysis, considering data on terrain, environment, climate, and water flow in the spatial, functional, and constructive aspects, supported by digital tools (Google Earth Pro 2024, AutoCAD 2024, SketchUP 2024, Sun Path 3D 2024, Photoshop 2024, and Twinmotion 2024). The results yielded a spatial–functional–constructive hydrological analysis; the water flow, constructed underground through a masonry system with an approximate angle of 60° in stone or pink granite, also maintained a negative slope, generally between 1% and 3%, which facilitated a rapid and direct distribution, presenting a greater flow with a width and depth of 30 cm, in addition to a vertical drop of 240 cm. The efficient use of water in agriculture through interconnected terraces ensured the population’s sustenance by approximately 80%. In conclusion, the analysis not only provides information on the infrastructure and water management but also addresses current issues.